Transformative Islamic Education for the Social Change Adjustment Strategy - Muhammad Adlan Nawawi (AL-ISHLAH: Jurnal Pendidikan, 2023)
The education system was never born in a vacuum. Awareness of the urgency of education accompanies the movement of social change which triggers the emergence of educational patterns that try to adapt to the demands and pressures of the times. The dynamics of democratization, the development of science and globalization also define an education system that is considered capable of responding to the challenges of the social and societal situation so as to produce learning figures who are able to adapt to the times and times. As a form of universal formulation, Islam from the beginning has called for the urgency of science and knowledge as an instrument for humans to interpret Islamic teachings. Allah SWT has also described in the drama the creation of the first human, Adam as, how instruments of science and knowledge are able to distinguish human existence from other creatures created by Him. Although it is not easy to go through, the creation of Adam leaves a myriad of mysteries that reveal the importance of education as a process capable of transforming humans into the best creatures and embodying divine qualities on earth as caliphs. In turn, the Islamic education system is able to contribute to the realization of an education system that is universal and able to accommodate the human needs of mankind. As a religion of mercy, Islam presents freedom as a form of individual responsibility in the face of various life challenges that often confine humanity to ignorance and backwardness. Transformation is an intrinsic value in Islam which becomes a form of strategy to adapt to various forms of social change.